Quantifying Graphitic Edge Exposure in Graphene-Based Materials and Its Role in Oxygen Reduction Reactions - Colavita, Paula (My University, 2016)
Oxygen electrochemistry is at the core of several emerging energy conversion technologies. The role of carbon nanostructures in the electrocatalysis of the oxygen reduction reaction is not well understood. Herein we report an investigation of the role of graphitic edges in oxygen electrochemistry. A new synthetic method was used to create all-carbon model electrode materials with controlled morphology. Electron microscopy results show that synthesized materials possess a high density of graphitic edges. Electrochemical intercalation experiments, however, indicate that the density of electroactive edges does not correlate positively with microscopy results. The materials were then characterized as electrodes for the oxygen reduction reaction in alkaline media. Results suggest that electrochemical determinations of edge and defect density more accurately predict electrocatalytic activity, thus suggesting that in situ characterization techniques are needed to understand the carbon/electrolyte interface.
PUBLISHED
Keywords: defects; electrocatalysis; graphene; graphitic edges; intercalation; ORR; oxygen reduction